The path of creative and educational performance of an illustrator - Porto-Oliveira, Edileusa (2025)
The development of creative potential can be influenced by aspects related to the individual himself and his experiences throughout life. The study aimed to identify and analyze aspects related to the path of creative and educational performance of an illustrator, focusing on the role of the teacher. The content of the lives to teach drawing, in the period of the Coronavirus pandemic, and a semi-structured interview were used. The results showed uniqueness in the development and expression in drawing, and in the way of teaching it: combinations between the new and the adapted in teaching and learning of drawing; tension between rules to design and freedom to create; ambivalent role of models as inhibiting and triggering the creation process.